Reduction of magnetizing inrush current in traction transformer - Basu, K. P.; Morris, Stella (2008)
In 25kv ac main line traction system the traction transformer located in the engine are repeatedly switched off and on during the normal run of the train due to presence of neutral section in the contact wire. The transformer draws inrush current several times the full-load value. Its enegization creates severe power quality problem in each time. The inrush current may be reduced to the full-load value either by using point-on-wave switching device or by connecting an external resistor in series with the primary circuit. The resistor is shorted within a few cycles of energization of the transformer to avoid voltage drop and losses during the steady-state operation of the transformer. Simulation results illustrate the effect of voltage and frequency variation on the production of inrush current. Only one circuit breaker with a delayed contact closing may be used for resistance switching.